Pengaruh Suhu Awal dan Waktu Infusi terhadap Aktivitas Antibakteri dan Antioksidan Ekstrak Minuman Herbal Daun Kopi Robusta - Lestari, Luh Gede Mening; Antara, Nyoman Semadi; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 1 (2021): MaretDO - 10.24843/JRMA.2021.v09.i01.p09, 2021)
The aim of this study was to find out initial infusion temperature and infusion time effects on of antibacterial and antioxidant activities the Robusta Coffee leaves herbal drink extract. This study also determined the best initial infusion temperature and infusion time that can produce Robusta Coffee leaves herbal drink extract with the best antibacterial and antioxidant activities. The study used factorial completely randomized design. The first factor is infusion temperature, consisting of 70± 2 °C, 80± 2 °C, and 90± 2 °C. The second factor is infusion time which consists of 5, 10, and 15 minutes. The data was analyzed by analysis of variance (ANOVA) and continued with Tukey test. The results showed that the treatment of initial infusion temperature, infusion time, and interaction between the two treatments had a very significant effect on antibacterial activity Abritrary Unit (AU) against Salmonella typhimurium and antioxidant activity Inhibitory Concentration 50 (IC 50 ) . The treatment of infusion time had a significant effect on antibacterial activity AU against Escherichia coli, but the initial infusion temperature and interaction between the two treatments had a very significant effect on it. The best treatment to infuse herbal drink of Robusta Coffee leaves as a source of antibacterial and antioxidant is using initial infusion temperature of 90± 2 °C and infusion time of 5 minutes with antibacterial activity AU against Escherichia coli of 1.248,34 ± 1 32,58 m m 2 /mL, antibacterial activity AU against Salmonella typhimurium of 1.473,37 ± 79,57 m m 2 /mL, and antioxidant activity IC 50 of 185,01 ± 1,66 ppm . Keywords: Robusta coffee leaves, herbal drink, antibacterial, antioxidant .